Evaluation of the decontamination efficacy of a portable air cleaner using 275-nm UVC-LED radiation against airborne Coronavirus and Influenza virus - Reissner, Janina; Reichelt, Benjamin; Siller, Paul; Brockmann, Gerrid; Kriegel, Martin; Roesler, Uwe; Friese, Anika (GMS Hygiene and Infection Control)
Background: The COVID-19 pandemic has highlighted the risk of airborne transmission of viruses, especially in public indoor spaces or healthcare settings. Effective indoor air purification systems are necessary to limit the spread of these pathogens, and the deployment of portable air cleaners (PACs) has increased rapidly since then. Germicidal ultraviolet (UV) radiation technologies have recently supplemented conventional air filtration technologies. Thus, the purpose of this study was to evaluate the air decontamination efficacy of a PAC using a 275-nm UVC-LED unit and fibrous-media air filters.